2016
DOI: 10.3174/ajnr.a4718
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intracranial Aneurysms in Patients with Connective Tissue Diseases: A Retrospective Study

Abstract: BACKGROUND AND PURPOSE:Few studies have examined the prevalence of intracranial aneurysms in connective tissue diseases such as Marfan syndrome, Ehlers-Danlos syndrome, neurofibromatosis type 1, and Loeys-Dietz syndrome. We studied the prevalence of intracranial aneurysms and other intracranial neurovascular pathologies such as arteriovenous malformations and intracranial dissections, in these 4 patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 10 publications
0
65
4
Order By: Relevance
“…Previous data on possible association between NF1 and IA are based on case reports and small patient series[6,7,10,24,2632], and have also been contested (Tables 3 and 4). [9] In a retrospective administrative database study from the USA, there were 28 (0,17%) SAH cases among 16918 NF1 patients over 18 years, which is within the range of SAH incidence in general population as well as our NF1 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on possible association between NF1 and IA are based on case reports and small patient series[6,7,10,24,2632], and have also been contested (Tables 3 and 4). [9] In a retrospective administrative database study from the USA, there were 28 (0,17%) SAH cases among 16918 NF1 patients over 18 years, which is within the range of SAH incidence in general population as well as our NF1 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial aneurysms have been reported in both classical and non-classical forms of EDS, but relatively speaking it is patients with the vascular subtype of EDS who are at the highest risk for IBA formation (Chen et al 2013;Kato et al 2001;Kim et al 2016;Lummus et al 2014;Mirza et al 1979;Oderich et al 2005;Schievink et al 1990Schievink et al , 2002. Kim et al (2016) found intracranial aneurysms in 12 individuals, seven of whom had vascular EDS, from a chart review of 99 EDS patients (mean age 41.7 years) who underwent brain imaging. There is currently no consensus on the clinical utility of screening for intracranial aneurysms among otherwise asymptomatic vascular EDS patients.…”
Section: Ehlers-danlos Syndromementioning
confidence: 99%
“…Cerebrovascular bleeding is the third leading cause of death in LDS patients, and intracranial aneurysms have been seen at a frequency ranging between 10 and 28 %. (Kim et al 2016;Loeys et al 2006;Rodrigues et al 2009;Vanakker et al 2011). Although further studies are needed to assess the clinical utility of screening LDS patients specifically for intracranial aneurysms, surveillance of each part of the vascular tree is currently recommended every two years (MacCarrick et al 2014).…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MRI enables detection of arterial aneurysms other than of the aortic root, eg, of intracranial aneurysms that have a high prevalence of 14% and grading of vessels tortuosity, which is associated with a more severe aortic phenotype in MFS 73,74…”
Section: Team Membersmentioning
confidence: 99%